Book Review: The System of Tourism Development Planning in Nepal (An Integrated Approach) - Srivastava, Nagendra Lal (Economic Literature, 2016)
The System of Tourism Development Planning in Nepal (An Integrated Approach), by Prof. Dr. Om Sharma. Kathmandu: Nawaraj Pandey, Ananda Chand and Saraswati Sharma, 2012. Pages 280 (including Bibliography, Index and Appendices). Price: NRs 300. Economic Literature, Vol. XI (67-68), June 2013